UJI KOMPOSISI BAHAN BAKU TERASIPADA ALAT PENUMBUK MEKANIS (Shrimp Paste Composition Test in Mechanical Pestle) - Siti Khadijah; Ainun Rohana; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT Shrimp paste is a kind of flavoring distinctive smell of food , fermented shrimp or fish with salt or a mixture of both , with or without other additives are permitted .The composition of the raw material paste is the main thing that needs to be considered in making paste. This research was purposed to test  the water content, organoleptic (color, tast, aroma) and the number of bacteria E.coli paste produced mechanical pestle.This study uses a completely randomized design (CRD) non factorial consisting of one factors: the composition of the raw material paste with 3 repetitions, that is A1 = 1 kg shrimp + 100 g of salt + 250 mL of water, A2 = 1 shrimp + kg 100 g of salt + 500 mL of water, A3 = 1 kg shrimp + 100 grams of salt + 750 mL of water. The parameters observed water content, organoleptic (color, taste, aroma) and the number of E. coli bacteria The results showed the percentage of water content ranged from 15.10 to 20.22 %; organoleptic value of color ranges from 2.67 to 4.2; organoleptic taste value ranging from 2.8 to 4.2; aroma organoleptic values ​​ranged from 2.7 to 4.06; and there are no E. coli cells in the resulting paste.  Keywords : Paste, Composition, Shrimp,Water.  ABSTRAK   Terasi adalah suatu jenis bahan penyedap makanan yang berbau khas, hasil fermentasi udang atau ikan atau campuran keduanya dengan garam, dengan atau tanpa bahan tambahan lain yang diijinkan. Komposisi bahan baku terasi merupakan hal utama yang perlu diperhatikan dalam pembuatan terasi. Penelitian ini untuk menguji kadar air, organoleptik (warna, rasa, aroma) dan jumlah bakteri E.coli terasi yang dihasilkan alat penumbuk mekanis. Penelitian ini menggunakan rancangan acak lengkap (RAL) non faktorial yang terdiri dari 1 faktor yaitu komposisi bahan baku terasi dengan 3 kali ulangan, yaitu A1= 1 kgudang+100 g garam+250 mL air, A2= 1 kg udang+100 ggaram+500 mL air, A3= 1 kg udang+100 g garam+750 mL air. Parameter yang diamati meliputi kadar air, organoleptik (warna, rasa, aroma) dan jumlah bakteri E.coli. Hasil penelitian menunjukkan persentase kadar air berkisar 15,10-20,22%; nilai organoleptik warna berkisar2,67-4,2; nilai organoleptik rasa berkisar  2,8-4,2; nilai organoleptik aroma berkisar 2,7-4,06; dan tidak terdapat bakteri E.coli pada terasi yang dihasilkan. Kata kunci: Terasi, Komposisi, Udang, Air.